Peran Collaborative Governance dalam Strategi Penanganan Kenakalan Remaja: Studi Kasus dan Implikasinya - Amanda Hermawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Juvenile delinquency is a complex problem and cannot only be solved by the government, it requires cooperation with parties that influence the problems that occur in juvenile delinquency including non-governmental institutions, families, schools, and the community. Therefore, this study was conducted to find out more about the role and strength of Collaborative Governance in dealing with juvenile delinquency. This study was conducted using the literature study method. The results of the study indicate that the role of Collaborative Governance is to unite the government, society, and non-governmental institutions in building the handling of juvenile delinquency. The government acts as the main facilitator, non-governmental institutions become parties that help carry out the handling of juvenile delinquency, and the community becomes service users and reporters. The implications of Collaborative Governance are socialization programs, skills training, counseling, and the formation of raid teams and environmental security teams. New things in this study are internal school resistance, social pressure on adolescents that have an impact, social stigma, and the inability of organizations to innovate. The success of this collaboration depends on the process of dialogue, trust, commitment, and monitoring evaluation.